Making Sense of Heterogeneity in the Influence of Childhood Abuse, Mental Health, and Drug Use on Women’s Offending Pathways - Broidy, Lisa Marie (Criminal justice and behavior, 2018)
Building from the developmental and life course literature and the feminist pathways literature, we aim to detail when and how exposure to abuse in childhood shapes female offending trajectories. Using data from 470 female offenders in Australia, our analyses assess whether internalizing symptoms and drug use help explain the link between early abuse and later offending among females. We then examine whether these links are most acute for females who onset early and evidence chronic involvement in offending. In support of the feminist pathways model, we find evidence for a pathway from early abuse to internalizing symptoms to drug use and then offending. In addition, and in line with the life course literature, we also find important differences in how these risks unfold across women, depending particularly on age of onset and offending chronicity. We reflect on the implications of our findings for theory and intervention with respect to female offending.